Defining priorities for global snow leopard conservation landscapes. (January 2020) - Li, Juan; Weckworth, Byron V.; McCarthy, Thomas M.; Liang, Xuchuang; Liu, Yanlin; Xing, Rui; Li, Diqiang; Zhang, Yuguang; Xue, Yadong; Jackson, Rodney; Xiao, Lingyun; Cheng, Chen; et al.
Abstract: The snow leopard ( Panthera uncia ) is an apex predator on the Tibetan Plateau and in the surrounding mountain ranges. It is listed as Vulnerable in the IUCN's Red List. The large home range and low population densities of this species mandate range-wide conservation prioritization. Two efforts for range-wide snow leopard conservation planning have been conducted based on expert opinion, but both were constrained by limited knowledge and the difficulty of evaluating complex processes, such as connectivity across large landscapes. Here, we compile >6000 snow leopard occurrence records from across its range and corresponding environmental covariates to build a model of global snow leopard habitat suitability. Using spatial prioritization tools, we identified seven large continuous habitat patches as global snow leopard Landscape Conservation Units (LCUs). Each LCU faces differing threat levels from poaching, anthropogenic development, and climate change. We identified ten potential inter-LCU linkages, and centrality analysis indicated that Tianshan-Pamir-Hindu Kush-Karakorum, Altai, and the linkage between them play a critical role in maintaining the global snow leopard habitat connectivity. However, international border fences, railways and major roads can fragment LCUs and potentially obstruct linkages. We propose LCU-specific conservation strategies and transboundary cooperation that should be highlighted in future snow leopard conservation. This effort represents the first range-wide, systematic landscape conservation plan for snow leopards, and provides a rigorous and analytically sound basis for further survey and evaluation. Graphical abstract: Unlabelled Image Highlights: Seven global snow leopard Landscape Conservation Units (LCUs) were identified. LCUs face threats from poaching, anthropogenic development and climate warming. Landscape connectivity patterns and ten linkages were identified. Border fences, railways and major roads may impede snow leopard dispersal. LCU-specific conservation strategies and transboundary cooperation were proposed.